Determination of Eugenol in Personal-Care Products by Dispersive Liquid-Liquid Microextraction Followed by Spectrophotometry Using p-Amino-N,N-dimethylaniline as a Derivatizing Agent - Bahaa Malik Altahir; Omar Abdulazeez; Sarmad Bahjat Dikran; Keith Edward Taylor (Universitas Gadjah Mada, 2021)
Two simple methods for the determination of eugenol were developed. The first depends on the oxidative coupling of eugenol with p-amino-N,N-dimethylaniline (PADA) in the presence of K3[Fe(CN)6]. A linear regression calibration plot for eugenol was constructed at 600 nm, within a concentration range of 0.25-2.50 μg.mL–1 and a correlation coefficient (r) value of 0.9988. The limits of detection (LOD) and quantitation (LOQ) were 0.086 and 0.284 μg.mL–1, respectively. The second method is based on the dispersive liquid-liquid microextraction of the derivatized oxidative coupling product of eugenol with PADA. Under the optimized extraction procedure, the extracted colored product was determined spectrophotometrically at 618 nm. A linear plot within a concentration range of 0.05–1.65 μg.mL–1 (r = 0.9997) was constructed. The LOD and LOQ were 0.053 and 0.177 μg.mL–1, respectively. Both methods were tested for the analysis of eugenol in commercial personal-care products, and the results confirmed that the procedures are accurate, precise, and reproducible (RSD < 1%).